Post-mortem quetiapine concentrations in hair segments of psychiatric patients — Correlation between hair concentration, dose and concentration in blood. (April 2018) - Günther, Kamilla Nyborg; Johansen, Sys Stybe; Nielsen, Marie Katrine Klose; Wicktor, Petra; Banner, Jytte; Linnet, Kristian
Highlights: Continuous individual concentration in hair was measured in six 1 cm hair segments. Quetiapine dose and hair concentration showed a positive correlation. Dose-adjusted hair concentrations were lower in dyed hair than in natural hair. Concentrations in blood and in the proximal hair segment were positively correlated. Abstract: Drug analysis in hair is useful when seeking to establish drug intake over a period of months to years. Segmental hair analysis can also document whether psychiatric patients are receiving a stable intake of antipsychotics. This study describes segmental analysis of the antipsychotic drug quetiapine in post-mortem hair samples from long-term quetiapine users by ultra-high performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) analysis. The aim was to obtain more knowledge on quetiapine concentrations in hair and to relate the concentration in hair to the administered dose and the post-mortem concentration in femoral blood. We analyzed hair samples from 22 deceased quetiapine-treated individuals, who were divided into two groups: natural hair colour and dyed/bleached hair. Two to six 1 cm long segments were analyzed per individual, depending on the length of the hair, with 6 cm corresponding to the last six months before death. The average daily quetiapine dose and average concentration in hair for the last six months prior to death were examined for potential correlation. Estimated doses ranged from 45 to 1040 mg quetiapine daily over the period, and the average concentration in hair ranged from 0.18 to 13 ng/mg. A significant positive correlation was observed between estimated daily dosage of quetiapine and average concentration in hair for individuals with natural hair colour (p = 0.00005), but statistical significance was not reached for individuals with dyed/bleached hair (p = 0.31). The individual coefficient of variation (CV) of the quetiapine concentrations between segments ranged from 3 to 34% for individuals with natural hair colour and 22–62% for individuals with dyed/bleached hair. Dose-adjusted concentrations in hair were significantly lower in females with dyed/bleached hair than in individuals with natural hair colour. The quetiapine concentrations in post-mortem femoral blood and in the proximal hair segment, segment 1 (S1), representing the last month before death were also investigated for correlation. A significant positive correlation was observed between quetiapine concentrations in blood at the time of death and concentrations in S1 for individuals with natural hair colour (p = 0.003) but not for individuals with dyed/bleached hair (p = 0.31). The blood concentrations of quetiapine ranged from 0.006 to 1.9 mg/kg, and the quetiapine concentrations in S1 ranged from 0.22 to 24 ng/mg. The results of this study suggest a positive correlation of quetiapine between both concentrations in hair and doses, and between proximal hair (S1) and blood concentrations, when conditions such as hair treatments are taken into consideration.